2011
DOI: 10.1111/j.1442-2050.2010.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of multiple channel pH monitoring for evaluation of ultra-distal reflux in patients after fundoplication for treatment of Barrett's esophagus

Abstract: Dysplasia and esophageal adenocarcinoma may arise in patients with Barrett's esophagus after fundoplication esophageal pH monitoring showing no acid in esophagus. This suggests the need to develop methodology to evaluate the occurrence of ultra-distal reflux (1cm above the LES). The objective of the study was to compare acid exposition in three different levels: 5cm above the upper border of the LES, 1cm above the LES and in the intrasphincteric region. Eleven patients with Barrett's esophagus after Nissen fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, there are currently no data to support such speculation. It has, however, been demonstrated that acid exposure is significantly greater in the distal and intrasphincteric segment of the esophagus [42, 51-53]. Fletcher at al.…”
Section: The Acid Pocketmentioning
confidence: 99%
“…However, there are currently no data to support such speculation. It has, however, been demonstrated that acid exposure is significantly greater in the distal and intrasphincteric segment of the esophagus [42, 51-53]. Fletcher at al.…”
Section: The Acid Pocketmentioning
confidence: 99%